High incidence of ankle arthropathy in mild and moderate haemophilia A - Ling, Min; Heysen, Jonathan Peter Hans; Duncan, Elizabeth Mary; Rodgers, Susan Elizabeth; Lloyd, John Viner (Thrombosis and Haemostasis, 2011)
A clinical study of patients with mild haemophilia A to document the frequency and severity of arthropathy has not been previously published. We studied ankle arthropathy in 34 patients with mild/moderate haemophilia A. The patients were assessed for the presence and severity of pain, and by the physical and radiological scoring systems for the evaluation of haemophilic arthropathy recommended by the World Federation of Haemophilia (WFH). Of the 34 patients, 16 (47%) had ankle pain, which was of moderate to severe degree in nine patients, and associated with limitation of physical activities in 13 patients. Of 33 patients examined by radiology 17 (52%) were positive for ankle arthropathy, and of these, 16 were also positive by the physical score. The presence and severity of ankle arthropathy was more common in patients with a one-stage factor VIII level of less than or equal to 11 IU/ dl. There was a significant relationship between the presence of ankle arthropathy and a history of bleeds into the ankle joint as a child. We conclude that arthropathy of the ankle in these patients is common, is often severe and disabling, and is due to episodes of bleeding into the ankle joint during childhood.
Keywords: Mild haemophilia; moderate haemophilia; ankle arthropathy; factor VIII; Pettersson score